Phenolic and Flavonoid Content of Black Mulberry (Morus nigra L.) Stem and Their Evaluation Antioxidant and Cytotoxic Profile - Syamsu Nur; Fitriyanti Jumaetri Sami; Marwati Marwati; Nursamsiar Nursamsiar; Alfat Fadri; Khairuddin Khairuddin (Borneo Journal of Pharmacy, 2022)
The black mulberry (Morus nigra) plant has been widely developed for its bioactivity as natural medicine. This study evaluated plant extracts' total phenolic and flavonoid content and their correlation to M. nigra stem's antioxidant activity and toxicity. Dry powder from the M. nigra stem was extracted by maceration with 96% ethanol to obtain a thick extract (TE) and fractionated using hexane (HF), ethyl acetate (EAF), and ethanol-aqueous (EF). The samples were analyzed for a compound using reagents and the determination of total phenolic and flavonoid content. The samples were evaluated for antioxidant activity using several parameters and their cytotoxic effects using the BSLT method. Identification of compounds in EAF was confirmed to contain phenolic, flavonoids, alkaloids, saponins, tannins, steroids, and terpenoids. EAF showed higher phenolic and flavonoid content than others. The evaluation of antioxidant activity showed that extracts and fractions from M. nigra stems showed the ability to reduce ions and free radicals. EF sample has activity in reducing Mo (IV) ion by TAC method of 98.82±0.53 µM/mg, indicating substantial antioxidant capacity. In addition, EAF samples showed potential activity in reducing DPPH, hydroxyl, and peroxide radicals in the β-carotene bleaching method with IC50 values of 12.13, 42.06, and 57.6 µg/mL, respectively. Similar activity was also seen in the cytotoxic effect of a robust EAF sample with an LC50 value of 16.31 µg/mL. The results show that EAF can be developed as a raw material for traditional medicine as an antioxidant and anticancer candidate with a significant flavonoid and phenolics content.